GROUP COUNSELING BASED ON MOSINTUWU VALUES TO REDUCE INTER-STUDENT CONFLICT - Kristanti Sateki; Ridwan Syahran; Mardi Lestari; Nurwahyuni (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This research develops a group counseling service based on Mosintuwu values, a local wisdom of Poso community in Central Sulawesi, to reduce inter-student conflicts in multicultural schools. Mosintuwu values including togetherness, tolerance, peace-loving, and mutual cooperation were chosen as the intervention foundation because they have proven effective as conflict resolution mechanisms in post-conflict Poso. The research problem focuses on how to integrate Mosintuwu values into a contextual and relevant group counseling format for adolescent students.The research employs the ADDIE model to produce a group counseling module consisting of four structured sessions. This module integrates group dynamics with Mosintuwu values through interactive lectures, experience sharing, case analysis, role-playing, and peer support formation. The research results are expected to provide theoretical contributions to the development of guidance and counseling based on Indonesian local culture, as well as practical benefits for school counselors and multicultural schools in creating a harmonious and tolerant learning environment.